Comparison of MALDI‐TOF mass spectrometry analysis of peripheral blood and bone marrow‐based flow cytometry for tracking measurable residual disease in patients with multiple myeloma. (5th February 2020) - Eveillard, Marion; Rustad, Even; Roshal, Mikhail; Zhang, Yanming; Ciardiello, Amanda; Korde, Neha; Hultcrantz, Malin; Lu, Sydney; Shah, Urvi; Hassoun, Hani; Smith, Eric; Lesokhin, Alexander; et al.
Summary: Matrix‐assisted laser desorption ionisation time‐of‐flight mass spectrometry (MALDI‐TOF MS) may soon replace routine electrophoretic methods for monitoring monoclonal proteins in patients with multiple myeloma. To further evaluate the clinical utility of this assay, we compared the performance of MALDI‐TOF‐MS head‐to‐head with an established bone marrow‐based measurable residual disease assay by flow cytometry (Flow‐BM‐MRD), using Memorial Sloan Kettering Cancer Center's 10‐color, single‐tube method. Our results suggest that MALDI‐TOF‐MS adds value to bone marrow‐based MRD testing and may be most useful for early detection of relapse in peripheral blood compared to current electrophoretic methods.